2020
DOI: 10.1590/s1413-41522020147587
|View full text |Cite
|
Sign up to set email alerts
|

Índice fuzzy de qualidade de água para ambiente lótico - IQAFAL

Abstract: The dissemination of information on water quality for a non-specialist audience is essential to support political and institutional actions for the management of aquatic environments. Therefore, water quality indices have been proposed since they are able to synthesize into a single value or category information, usually described from an extensive set of water quality variables. This research proposes a new water quality index, based on fuzzy logic, aimed at lotic environments, developed through the collabora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
0
1
0
6
Order By: Relevance
“…This is an example of models with greater expert intervention which can have its rules redesigned by using fuzzy logic. Pessoa et al [90] developed a fuzzy water quality index for lotic environments based on the CETESB deterministic water quality index. It was identified that the fuzzy application avoided the attenuation that variables classified in "critical conditions" suffer under the influence of other variables classified in "good conditions."…”
Section: How Does the Feedback Between The Stages Of The Open-minded Roadmap Support The Decision Making Process?mentioning
confidence: 99%
“…This is an example of models with greater expert intervention which can have its rules redesigned by using fuzzy logic. Pessoa et al [90] developed a fuzzy water quality index for lotic environments based on the CETESB deterministic water quality index. It was identified that the fuzzy application avoided the attenuation that variables classified in "critical conditions" suffer under the influence of other variables classified in "good conditions."…”
Section: How Does the Feedback Between The Stages Of The Open-minded Roadmap Support The Decision Making Process?mentioning
confidence: 99%
“…A água é um elemento imprescindível para a humanidade, entre outros motivos, por ser um recurso natural cujo consumo diário é vital para a sobrevivência de todos os indivíduos (Pessoa et al, 2020). Os usos múltiplos das águas superficiais brasileiras estão assegurados pela Lei nº 9.433, de 08 de janeiro de 1997 (Brasil, 1997), que instituiu a Política Nacional de Recursos Hídricos.…”
Section: Introductionunclassified
“…Este índice sumariza um conjunto amplo de atributos de qualidade de água a um único padrão indicador, possibilitando o enquadramento das águas em classes ou categorias (Gloria et al, 2017). Deste modo, o IQA auxilia gestores na tomada de decisões por fornecer resultados de fácil interpretação que permitem prever as condições do manancial superficial (Pessoa et al, 2020;Valentini et al, 2021).…”
Section: Introductionunclassified
“…Além do mais, os resultados obtidos podem se traduzir em propostas de ações concretas que visam mitigar os efeitos da utilização indiscriminada dos recursos hídricos, buscando equilíbrio entre o desenvolvimento econômico, social e a conservação ambiental (PESSOA, 2010).…”
Section: Introductionunclassified
“…No entanto, essa situação gera uma dificuldade intrínseca de comunicação entre aqueles que produzem e detêm o conhecimento sobre a qualidade das águas e aqueles que não são especialistas em qualidade de água, mas necessitam desse conhecimento para subsidiar suas ações gerenciais (PESSOA, 2010).…”
Section: Introductionunclassified